Ni3InC0.5 wave-absorbing material and preparation method thereof

Ni3InC0.5 absorbing material was prepared by solution precipitation method, which solved the problems of side reactions and performance influence in solid phase method, achieved efficient absorbing performance, and showed excellent electromagnetic wave absorption effect.

CN119263282AActive Publication Date: 2025-01-07YANTAI UNIV

Patent Information

Application Number
CN202411642773.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-07
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

In the prior art, the intrinsic electromagnetic parameters and wave absorption properties of Ni3InC0.5 are unknown, and the solid-phase preparation method has problems of side reactions and material properties.

Method used

Ni3InC0.5 absorbing material was prepared by solution precipitation method. By controlling the molar ratio of nickel and indium, DMF was used as solvent, PTA, TEA as ligand and alkaline source, and filtration was carried out after magnetic stirring and circulating water, and then in a nitrogen atmosphere. Ni3InC0.5 material with spherical and rod-shaped particles was prepared by calcination.

Benefits of technology

The efficient absorption performance of Ni3InC0.5 material was achieved, with a minimum reflection loss of -35.37 dB and an effective absorption bandwidth of 4.6 GHz, demonstrating its potential in the field of absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263282A_ABST
    Figure CN119263282A_ABST
Patent Text Reader

Abstract

The invention discloses a Ni3InC0.5 wave-absorbing material and a preparation method thereof, and the preparation method comprises the following steps: (1) dispersing Ni (CH3COO) 2.4 H2O and In (CH3COO) 2.6 H2O into N, N-dimethylformamide (DMF), and magnetically stirring to obtain a liquid A; (2) dispersing terephthalic acid (PTA) and triethylamine (TEA) into DMF, and magnetically stirring to obtain liquid B; (3) pouring the liquid B into the liquid A, and continuously stirring to obtain a Ni3InC0.5 precursor solution; (4) putting the solution obtained in the step (3) into a circulating water suction filter for suction filtration to obtain a gelatinous sample; and (5) taking a sample obtained in the step (4), calcining the sample in a nitrogen atmosphere, and naturally cooling the sample to room temperature to obtain Ni3InC0.5. The method has the characteristics of simple process and low cost, and the material is applied to the field of wave absorption for the first time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wave absorbing materials, and in particular to a Ni3InC 0.5 Wave absorbing material and preparation method. Background Art

[0002] With the development of communication technology and modern science and technology, constructing absorbing materials with light weight, strong absorption, thin thickness and wide frequency characteristics is of great significance to weaken the impact of electromagnetic radiation.

[0003] In recent years, metal carbides with multiple loss mechanisms such as dielectric loss and magnetic loss have emerged as non-stoichiometric bimetallic carbides Ni3ZnC 0.7 It has the advantages of precise control of composition, low synthesis cost, and easier formation of defects, so it has great development potential in the field of microwave absorption. Some researchers have combined it with a variety of carbon materials to enhance the dielectric properties and obtained excellent microwave absorption performance.

[0004] Ni3InC 0.5 Ni3ZnC 0.7 There are many similarities, but they are more widely used in catalysis, batteries and other energy fields, and have never been used in the field of microwave absorption, so there is a research gap.

[0005] At present, Ni3InC 0.5 The intrinsic electromagnetic parameters and wave absorption performance of Ni3InC are still unknown. 0.5 Among the preparation methods, the solid phase method (https: / / doi.org / 10.1039 / d3dt01331f) is widely used. The raw materials for its synthesis are hydroxides of Ni and In. However, hydroxides may undergo side reactions under certain reaction conditions, which not only reduces the yield and purity of the product, but may also affect the performance of the final material. At the same time, hydroxides may be more susceptible to moisture absorption or decomposition during storage and handling. Summary of the invention

[0006] In order to overcome the above technical problems, the object of the present invention is to provide a Ni3InC 0.5 The invention discloses a wave absorbing material and a preparation method thereof. The material preparation method has the characteristics of good chemical uniformity and simple operation.

[0007] The technical solution adopted by the present invention is: A Ni3InC 0.5The absorbing material is mainly spherical particles. A few spherical particles are sintered and agglomerated to form a small number of rod-shaped particles. The diameter of the spherical particles is about 50-80 nm, the surface is relatively smooth and evenly distributed; the length of the rod-shaped particles is about 100-150 nm, the diameter is 50-80 nm, and the surface of both particles is Ni3InC 0.5 Mutually.

[0008] Spherical particles have good symmetry and can evenly scatter incident electromagnetic waves, reduce signal reflection, and improve wave absorption efficiency. The presence of rod-shaped particles can introduce asymmetry, promote multiple reflections and scattering of electromagnetic waves, and further enhance the wave absorption effect.

[0009] A Ni3InC 0.5 The method for preparing the wave absorbing material comprises the following steps: (1) Disperse Ni(CH3COO)2·4H2O and In(CH3COO)2·6H2O in N, N-dimethylformamide (DMF) and obtain liquid A after magnetic stirring; (2) Dispersing terephthalic acid (PTA) and triethylamine (TEA) in DMF, and obtaining liquid B after magnetic stirring; (3) Pour the liquid B obtained in step (2) into the liquid A obtained in step (1) and continue stirring to obtain Ni3InC 0.5 Precursor solution; (4) Ni3InC obtained in step (3) 0.5 The precursor solution is placed in a circulating water filter and filtered to obtain a gel sample; (5) The gel sample obtained in step (4) was calcined under nitrogen atmosphere and naturally cooled to room temperature to obtain Ni3InC 0.5 Wave absorbing material.

[0010] In the step (1), Ni(CH3COO)2·4H2O and In(CH3COO)2·6H2O are dispersed in 125-300 mL DMF; wherein the molar ratio of Ni(CH3COO)2·4H2O to In(CH3COO)2·6H2O is 3:1.

[0011] By precisely controlling the molar ratio of nickel (Ni) and indium (In), it is possible to ensure that Ni3InC with a specific chemical composition is formed in the subsequent reaction. 0.5 Precursor. During the synthesis process, DMF, as a solvent, helps dissolve and mix the metal salts Ni(CH3COO)2·4H2O and In(CH3COO)2·6H2O, providing a homogeneous reaction environment for the subsequent coordination reaction.

[0012] In the step (1), magnetic stirring is performed for 0.5-1 h.

[0013] In step (2), 7-10 mmol PTA and 2-4 ml TEA are dispersed in 100-200 ml DMF. PTA is an organic acid that can participate in the reaction as a ligand or auxiliary ligand during the synthesis process, which helps to form a stable metal complex; while TEA is an alkali source in the reaction and is used to adjust the pH value of the reaction system. The setting of this ratio is more conducive to the complexation and stability of the product.

[0014] In the step (2), magnetic stirring is performed for 0.5-1 h.

[0015] In the step (3), magnetic stirring is performed for 1-20 h.

[0016] In the step (5), the sample obtained in step (4) is heated to 700-900°C at a heating rate of 5°C / min under nitrogen atmosphere and kept at this temperature for 10-12 hours. At this calcination time and temperature, single-phase Ni3InC 0.5 .

[0017] The Ni3InC prepared in step (5) 0.5 The material is used in the field of microwave absorption.

[0018] Beneficial effects of the present invention: The outstanding essential feature of the present invention is that Ni3InC is prepared by solution precipitation method for the first time. 0.5 Its intrinsic electromagnetic parameters and wave absorption performance were tested. Combined with the density of the material, it was found that in m(Ni3InC 0.5 ):m(paraffin)=20-60% condition, Ni3InC 0.5 The minimum reflection loss is -35.37 dB and the effective absorption bandwidth is 4.6 GHz, which confirms that Ni3InC 0.5 It has great development potential in the field of wave absorption. The excellent wave absorption performance is mainly attributed to the following aspects: First, Ni3InC 0.5 The Ni in the material has excess 3d orbital unpaired electrons, which induce unique polarization losses, thus having a positive effect on the electromagnetic wave absorption performance; secondly, in the high frequency range, Ni3InC 0.5 The metal Ni and In in the material have good electrical conductivity, which will produce eddy current effect in the external electromagnetic field. This eddy current effect will cause electromagnetic energy to be converted into heat energy, thus generating magnetic loss; at the same time, Ni3InC 0.5 The interface between particles will cause polarization relaxation, which is beneficial to the attenuation of electromagnetic waves through polarization loss; in addition, the existence of rod-shaped particles dissipates multiple reflections and scattering, enhancing the electromagnetic absorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Ni3InC obtained in Example 1 0.5 X-ray diffraction spectrum of the material.

[0020] Figure 2 Ni3InC obtained in Example 1 0.5 Scanning electron microscope image of the material.

[0021] Figure 3 In Example 2, when m(Ni3InC 0.5 ):m(paraffin)=30%, Ni3InC 0.5 Material properties diagram.

[0022] Figure 4 In Example 3, when m(Ni3InC 0.5 ):m(paraffin)=40%, Ni3InC 0.5 Material properties diagram.

[0023] Figure 5 In Example 4, when m(Ni3InC 0.5 ):m(paraffin)=50%, Ni3InC 0.5 Material properties diagram. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0025] (1) Disperse 11.25 mmol Ni(CH3COO)2·4H2O and 3.75 mmol In(CH3COO)2·6H2O in 125 mL DMF and stir magnetically for 0.5 h to obtain liquid A.

[0026] (2) Disperse 9 mmol PTA and 2.125 ml TEA in 100 ml DMF and stir magnetically for 0.5 h to obtain liquid B.

[0027] (3) Pour liquid B into liquid A and continue stirring for 20 h to obtain Ni3InC 0.5 Precursor solution.

[0028] (4) The solution obtained in step (3) is placed in a circulating water filter and filtered to obtain a gel sample.

[0029] (5) Take the sample obtained in step (4), heat it to 700 °C at a rate of 5 °C / min in a nitrogen atmosphere and keep it for 10 h. After cooling it naturally to room temperature, Ni3InC 0.5 .

[0030] The synthesized Ni3InC 0.5 The material was characterized by X-ray diffractometer, and the results were as follows Figure 1 As shown, diffraction peaks appear at 2θ=23.51°, 33.5°, 41.34°, 48.1°, 70.42° and 85.02°, which can be indexed to the standard card Ni3InC 0.5 PDF#28-0468, and no other impurities, proving that pure phase Ni3InC was successfully prepared 0.5 Then, Ni3InC 0.5 The morphological characterization was performed, such as Figure 2 As shown in the figure, it can be seen that under the low-power scanning electron microscope, the main particles are spherical particles, with a small amount of rod-shaped particles. After magnification, it is found that the size of the spherical particles is about 50-80 nm, the surface is relatively smooth and evenly distributed. Example

[0031] Synthesis of Ni3InC 0.5 The specific steps for preparing the test ring with a paraffin filling ratio of 30% are as follows: (1) Disperse 11.25 mmol Ni(CH3COO)2·4H2O and 3.75 mmol In(CH3COO)2·6H2O in 125 mL DMF and stir magnetically for 0.5 h to obtain liquid A.

[0032] (2) Disperse 9 mmol PTA and 2.125 ml TEA in 100 ml DMF and stir magnetically for 0.5 h to obtain liquid B.

[0033] (3) Pour liquid B into liquid A and continue stirring for 1 h to obtain Ni3InC 0.5 Precursor solution.

[0034] (4) The solution obtained in step (3) is placed in a circulating water filter and filtered to obtain a gel sample.

[0035] (5) Take the sample obtained in step (4), heat it to 700 °C at a rate of 5 °C / min in a nitrogen atmosphere and keep it for 10 h. After cooling it naturally to room temperature, Ni3InC 0.5 .

[0036] (6) Weigh 0.03 g Ni3InC 0.5 powder and 0.07 g paraffin (m(Ni3InC 0.5 ):m(paraffin)=30%) and mix, place the mixture in a container, and melt the paraffin using the heating function of a constant temperature magnetic stirrer. Stir gently with a medicine spoon until the mixture is evenly mixed, place it in a mold, and apply pressure to prepare a paraffin filling ratio of 30% Ni3InC with an outer diameter of 7 mm and an inner diameter of 3.04 mm. 0.5 Test ring.

[0037] The paraffin filling ratio of 30% Ni3InC prepared in Example 1 was analyzed by vector network analyzer (3656D). 0.5 The test ring is used to test the wave absorption performance. Figure 3 Display, Ni3InC 0.5 The minimum reflection loss is -38.76 dB and the effective absorption bandwidth is 3.82 GHz. Example

[0038] Synthesis of Ni3InC 0.5 The specific steps for preparing the test ring with a paraffin filling ratio of 40% are as follows: (1) Disperse 11.25 mmol Ni(CH3COO)2·4H2O and 3.75 mmol In(CH3COO)2·6H2O in 125 mL DMF and stir magnetically for 0.5 h to obtain liquid A.

[0039] (2) Disperse 9 mmol PTA and 2.125 ml TEA in 100 ml DMF and stir magnetically for 0.5 h to obtain liquid B.

[0040] (3) Pour liquid B into liquid A and continue stirring for 1 h to obtain Ni3InC 0.5 Precursor solution.

[0041] (4) The solution obtained in step (3) is placed in a circulating water filter and filtered to obtain a gel sample.

[0042] (5) Take the sample obtained in step (4), heat it to 700 °C at a rate of 5 °C / min in a nitrogen atmosphere and keep it for 10 h. After cooling it naturally to room temperature, Ni3InC 0.5 .

[0043] (6) Weigh 0.04 g Ni3InC 0.5 powder and 0.06 g paraffin (m(Ni3InC 0.5):m(paraffin)=40%) and mix, place the mixture in a container, and melt the paraffin using the heating function of a constant temperature magnetic stirrer. Stir gently with a medicine spoon until the mixture is evenly mixed, place it in a mold, and apply pressure to prepare a paraffin filling ratio of 40% Ni3InC with an outer diameter of 7 mm and an inner diameter of 3.04 mm. 0.5 Test ring.

[0044] The paraffin filling ratio of 40% Ni3InC prepared in Example 2 was analyzed by vector network analyzer (3656D). 0.5 The test ring is used to test the wave absorption performance. Figure 4 Display, Ni3InC 0.5 The minimum reflection loss is -35.37 dB and the effective absorption bandwidth is 4.6 GHz. Example

[0045] Synthesis of Ni3InC 0.5 The specific steps for preparing the test ring with a paraffin filling ratio of 50% are as follows: (1) Disperse 11.25 mmol Ni(CH3COO)2·4H2O and 3.75 mmol In(CH3COO)2·6H2O in 125 mL DMF and stir magnetically for 0.5 h to obtain liquid A.

[0046] (2) Disperse 9 mmol PTA and 2.125 ml TEA in 100 ml DMF and stir magnetically for 0.5 h to obtain liquid B.

[0047] (3) Pour liquid B into liquid A and continue stirring for 1 h to obtain Ni3InC 0.5 Precursor solution.

[0048] (4) The solution obtained in step (3) is placed in a circulating water filter and filtered to obtain a gel sample.

[0049] (5) Take the sample obtained in step (4), heat it to 700 °C at a rate of 5 °C / min in a nitrogen atmosphere and keep it for 10 h. After cooling it naturally to room temperature, Ni3InC 0.5 .

[0050] (6) Weigh 0.05 g Ni3InC 0.5 powder and 0.05 g paraffin (m(Ni3InC 0.5 ):m(paraffin)=50%) and mix, place the mixture in a container, and melt the paraffin using the heating function of a constant temperature magnetic stirrer. Stir gently with a medicine spoon until the mixture is evenly mixed, place it in a mold, and apply pressure to prepare a paraffin filling ratio of 50% Ni3InC with an outer diameter of 7 mm and an inner diameter of 3.04 mm. 0.5Test ring.

[0051] The paraffin filling ratio of 50% Ni3InC prepared in Example 3 was analyzed by vector network analyzer (3656D). 0.5 The test ring is used to test the wave absorption performance. Figure 5 Display, Ni3InC 0.5 The minimum reflection loss is -19.45 dB and the effective absorption bandwidth is 3.98 GHz.

[0052] In summary, the above are only embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A Ni3InC 0.5 The wave absorbing material is characterized in that The main particles are spherical particles, and a few spherical particles are sintered and agglomerated to form a small number of rod-shaped particles. The diameter of the spherical particles is about 50-80 nm, the surface is relatively smooth and evenly distributed; the length of the rod-shaped particles is about 100-150 nm, the diameter is 50-80 nm, and the surface of both particles is Ni3InC 0.5 Mutually.

2. A Ni3InC according to claim 1 0.5 The method for preparing a wave absorbing material is characterized in that: The steps include: (1) Disperse Ni(CH3COO)2·4H2O and In(CH3COO)2·6H2O in N, N-dimethylformamide (DMF) and obtain liquid A after magnetic stirring; (2) Dispersing terephthalic acid (PTA) and triethylamine (TEA) in DMF, and obtaining liquid B after magnetic stirring; (3) Pour the liquid B obtained in step (2) into the liquid A obtained in step (1) and continue stirring to obtain Ni3InC 0.5 Precursor solution; (4) Ni3InC obtained in step (3) 0.5 The precursor solution is placed in a circulating water filter and filtered to obtain a gel sample; (5) The gel sample obtained in step (4) was calcined in a nitrogen atmosphere and naturally cooled to room temperature to obtain Ni3InC 0.5 Wave absorbing material.

3. A Ni3InC according to claim 2 0.5 The method for preparing a wave absorbing material is characterized in that: In the step (1), Ni(CH3COO)2·4H2O and In(CH3COO)2·6H2O are dispersed in 125-300 mL DMF; wherein the molar ratio of Ni(CH3COO)2·4H2O to In(CH3COO)2·6H2O is 3:1; In the step (1), magnetic stirring is performed for 0.5-1 h.

4. A Ni3InC according to claim 2 0.5 The method for preparing a wave absorbing material is characterized in that: In the step (2), 7-10 mmol PTA and 2-4 ml TEA are dispersed in 100-200 ml DMF; In the step (2), magnetic stirring is performed for 0.5-1 h.

5. A Ni3InC according to claim 2 0.5 The method for preparing a wave absorbing material is characterized in that: In the step (3), magnetic stirring is performed for 1-20 h.

6. A Ni3InC according to claim 2 0.5 The method for preparing a wave absorbing material is characterized in that: In the step (5), the sample obtained in step (4) is heated to 700-900°C at a heating rate of 5°C / min under nitrogen atmosphere and kept at this temperature for 10-12 hours. At this calcination time and temperature, single-phase Ni3InC 0.5 .

7. A Ni3InC according to any one of claims 1 to 6 0.5 The application of the absorbing material is characterized by: The Ni3InC 0.5 The material is used in the field of microwave absorption.

Citation Information

Patent Citations

  • A nickel-zinc ferrite wave-absorbing material and a preparation method thereof

    CN109037961A

  • Supported nickel-based alloy catalyst as well as preparation method and application thereof

    CN109675569A

  • NiCo / C@CNT double-conductive network hierarchical structure material, and preparation method and application thereof

    CN110669474A

  • Sponge-derived carbon / nickel-zinc composite carbide material containing carbon nanofibers and preparation method of sponge-derived carbon / nickel-zinc composite carbide material

    CN114940621A

  • Preparation method and application of chocolate ball type silicon carbide multilayer composite wave-absorbing material

    CN115074085A

Cited By

  • Ni3GaC0.5 / Ni3Ga5 / Ni composite microsphere wave-absorbing material as well as preparation method and application thereof

    CN120961914A